Ethnoveterinary plants in traditional practices by various tribes in the western Himalaya of Jammu & Kashmir India - R.L. Bhellum; B.L. Bhellum (International Journal of Pharma and Bio Sciences, 2020)
Jammu and Kashmir is one of the mountainous states occupying most prominent position in North-West Indian Himalayas, bestowed with rich traditional knowledge base in plant resources. The region is inhabited by large number of tribes. Perusal of past experience developed their own system of medical practices for treatment of human ailments and diseases of domesticated animals. Ethno-veterinary exploration carried out during the past many years have brought to light over 66 plant species for treatment of live stock for better milk production, wool, meat and reproduction of animals and genetic make-up with special thrust on immunity against fatal diseases. The present paper is based on ethno-veterinary field practice in Animal Husbandry Department, Jammu and Kashmir, mostly in Hilly terrain of Rajouri-Poonch of Jammu province and information accrued from Gujjar, Bakerwals, Gaddhi tribes and other rural people who had been engaged in Animals and Poultry rearing. The identification of plant species, local name, and specific preparations of dosages from plants part and mode of Administration were discussed with local healers of the area, veterinarian who visited high land and alpine pastures frequently to attend exigencies such as outbreak of diseases etc. and the authorities who are well-versed with the flora of Jammu and Kashmir.